METHODOLOGY OF DEVELOPMENT OF SOCIAL COMPETENCE IN FUTURE ENGLISH LANGUAGE TEACHERS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Innovative training of future specialists at the international level, modern the world's leading higher education institutions for the implementation of education and of future pedagogues in research conducted by scientific centers the criteria of professional skills, the problems of creating an innovative educational environment are international special importance is attached to the introduction of the requirements of educational standards.